Analisis Pemahaman dan Kepatuhan Pajak Bendahara Pemerintah: (Studi di Kota Padang dan Kota Solok) - Cheisviyanny, Charoline (Unand Press, 2018)
This research aims to analyze tax knowledge and tax compliance of government treasurers and to analyze their relationships. The objects of the research were regional work units (OPDs) in Padang and Solok. The respondents were OPD’s treasurers with 37 people in Padang and 31 people in Solok. Data was collected by surveys and interviews. The result showed that (1) the tax knowledge of treasurers’ is in “enough” level; (2) all tax obligations have been implemented by treasurers, except tax reporting, (3) there is no relationship between tax knowledge and tax compliance. It suggested to enhance tax socialization and to add the objects of the research for further researches. Keywords: tax knowledge, tax compliance, treasurer